Colágeno de frango: uma alternativa para agregar valor aos subprodutos da indústria avícola - Schmidt, Michele Mantelli (2018)
The process of elaboration of mechanically separated meat (MSM) generates 15% to 45% of residue. Obtaining collagen and protein hydrolysates is a promising alternative to add value to this residue. The methods to obtain the collagen and hydrolysates are based on chemical or enzymatic hydrolysis, another method that has been highlighted is the ultrasound method, which enables process time reduction and increase of yield. In this context, this project aims the obtaining of protein hydrolysates and collagen from residue of MSM of chicken through enzymatic hydrolysis assisted or not by ultrasound. The collagen of MSM residue of chicken extracted with pepsin presented good performance and high thermal stability, the triple helical structure was conserved, which was confirmed by electrophoresis (SDS-PAGE) and Fourier transform infrared (FTIR) analyzes, the collagen being composed mainly by collagen of type I. Concerning to the functionality, the collagen presented acid pH solubility and emulsifying activity index higher than conventional gelatins. Pre-treatment with ultrasound and time of enzymatic extraction with pepsin had a positive effect on the extraction yield of the collagen without affecting its integrity. The MSM residue collagen was hydrolyzed with the enzymes Alcalase® and Flavourzyme®, the highest degree of hydrolysis was obtained with Alcalase®. Differential scanning calorimetry (DSC), FTIR and SDS-PAGE confirmed the hydrolysis, which also affected the functionality of the hydrolyzed collagen, which showed a decrease in viscosity and foaming ability and an improvement in the emulsifying activity index. Thus, the MSM residue of chicken proved to be a technologically source viable for the extraction of collagen and the collagen of this residue was promising as an alternative to traditional collagens with potential for industrial application. Obtaining hydrolysates from collagen of MSM residue of chicken using Alcalase® and Flavourzyme® proved to be viable, with potential for future application.